Separation of Craniopagus Twins: A Clinical, Legal, and Ethical Conundrum - Johnson, Reuben (Cambridge quarterly of healthcare ethics, 2016)
Separation of craniopagus twins is fraught by ethical issues. The surgery is high risk and may involve the sacrifice of one twin. We review surgical successes in separation of craniopagus twins and consider ethical and legal concepts affecting the decision to undertake such procedures. Our discussion considers how Gillett’s potentiality principle and the concept of moral permissibility may be used to arrive at fair and realistic decisions.